Comparative phylogenomics of the CBL-CIPK calcium-decoding network in the moss Physcomitrella, Arabidopsis, and other green lineages - Kleist, Thomas J.; Spencley, Andrew L.; Luan, Sheng (Frontiers in Plant Science, 2014)
Land plants have evolved a host of anatomical and molecular adaptations for terrestrial growth. Many of these adaptations are believed to be elaborations of features that were present in their algal-like progenitors. In the model plant Arabidopsis, 10 Calcineurin B-Like proteins (CBLs) function as calcium sensors and modulate the activity of 26 CBL-Interacting Protein Kinases (CIPKs). The CBL-CIPK network coordinates environmental responses and helps maintain proper ion balances, especially during abiotic stress. We identified and analyzed CBL and CIPK homologs in green lineages, including CBLs and CIPKs from charophyte green algae, the closest living relatives of land plants. Phylogenomic evidence suggests that the network expanded from a small module, likely a single CBL-CIPK pair, present in the ancestor of modern plants and algae. Extreme conservation of the NAF motif, which mediates CBL-CIPK physical interactions, among all identified CIPKs supports the interpretation of CBL and CIPK homologs in green algae and early diverging land plants as functionally linked network components. We identified the full complement of CBL and CIPK loci in the genome of Physcomitrella, a model moss. These analyses demonstrate the strong effects of a recent moss whole genome duplication: CBL and CIPK loci appear in cognate pairs, some of which appear to be pseudogenes, with high sequence similarity. We cloned all full-length transcripts from these loci and performed yeast two-hybrid analyses to demonstrate CBL-CIPK interactions and identify specific connections within the network. Using phylogenomics, we have identified three ancient types of CBLs that are discernible by N-terminal localization motifs and a “green algal-type” clade of CIPKs with members from Physcomitrella and Arabidopsis.